PERANAN WANITA USAHA PENGOLAHAN IKAN ASAP DALAM PENINGKATAN PENDAPATAN RUMAH TANGGA DI DESA LIANG DAN DESA LIANG ULU KECAMATAN KOTA BANGUN - Nur Tina Sari Hartati; Said Abdusysyahid; Wahyu Fahrizal (2339-1324, 2022)
Kota Bangun District, particularly Liang Village and Liang Ulu Village, has significant potential in obtaining fishery products so that they easily obtain risk and have fluctuating income pattern. This encourages women, including the housewives to take role in increasing the family income. The objective of the current research is to know the women’s role in smoked fish processing business to increase the household income and to know the contribution level of women income in the marketing channel of smoked fish business. Furthermore, this research was carried out using saturated sampling/ census. Meanwhile, the data analysis was done through income and marketing channel analysis method. The women’s role in smoked fish processing business is as the direct business actor with the average monthly income is IDR 2,666,000. Meanwhile, the contribution level of the women in the smoked fish processing business was at the average of 32.39%. In this case, their role starts from making the packaging, determining the price, and marketing the smoked fish production results. The marketing channel of smoked fish processing business is the channel at level 0 (zero), which is the producer to final consumer.